Lifting up the lives of extremely disadvantaged youth: The role of staying in school longer - Jan C. van Ours; Julie Moschion (Tinbergen Institute, 2025)
Using a sample of Australians who display high rates of early school-leaving, we compare the trajectories of respondents who left school at each incremental age between 14 and 17 with respondents who left at 18 years old or more, in terms of homelessness, incarceration, substance use and mental health issues. Leveraging recent methodological advances, we estimate a staggered difference-in-difference to: eliminate biases arising from reverse causality or unobserved timeinvariant unobserved heterogeneity and account for heterogenous treatment effects across cohorts and time. Results indicate that leaving school before age 18 increases males' likelihood of experiencing homeless, being incarcerated, using cannabis daily and illegal street drugs weekly several years after school-leaving. In contrast, for females the difference-in-difference strategy eliminates the correlations between school-leaving age and their outcomes, providing some support for a causal interpretation of our findings. To minimise concerns that gender specific timevarying unobserved heterogeneity may be driving our results, we also show that while the occurrence and timing of parental separation and other adverse behaviours coincide with early school-leaving, our results are robust to accounting for these. Taken together, our findings suggest that preventing early school-leaving can help disadvantaged youth break cycles of multidimensional disadvantage.
Keywords: C23; I12; I24; I32; 330; Education; Homelessness; Substance use; Incarceration; Mental health; Australia